2016
DOI: 10.1534/g3.115.024067
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Classical Mutant in the Industrial HostAspergillus nigerby Systems Genetics: LaeA Is Required for Citric Acid Production and Regulates the Formation of Some Secondary Metabolites

Abstract: The asexual filamentous fungus Aspergillus niger is an important industrial cell factory for citric acid production. In this study, we genetically characterized a UV-generated A. niger mutant that was originally isolated as a nonacidifying mutant, which is a desirable trait for industrial enzyme production. Physiological analysis showed that this mutant did not secrete large amounts of citric acid and oxalic acid, thus explaining the nonacidifying phenotype. As traditional complementation approaches to charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 81 publications
4
62
1
Order By: Relevance
“…Regulatory effects of laeA ortholog on secretion of cellulases have been shown in T. reesei [37] and the effects on mycotoxins have also been shown previously in A. carbonarius [9]. Findings of our study suggest that the regulatory effect extends even further to production of organic acids as it is also suggested by Niu et al [30] and Dai and Baker [10]. It was also shown that at the same time as LaeA regulates endoglucanase in A. carbonarius, it does not regulate two of the other important cell wall degrading enzymes, namely beta-glucosidases and xylanases.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Regulatory effects of laeA ortholog on secretion of cellulases have been shown in T. reesei [37] and the effects on mycotoxins have also been shown previously in A. carbonarius [9]. Findings of our study suggest that the regulatory effect extends even further to production of organic acids as it is also suggested by Niu et al [30] and Dai and Baker [10]. It was also shown that at the same time as LaeA regulates endoglucanase in A. carbonarius, it does not regulate two of the other important cell wall degrading enzymes, namely beta-glucosidases and xylanases.…”
Section: Discussionsupporting
confidence: 89%
“…In a recent patent in A. niger, the overexpression of laeA alone or together with the disruption of alg3 contributed to an increase in citric acid production indicating that it is not only secondary metabolites, reproduction and morphology that are regulated by LaeA [10]. A point mutation in the laeA gene in A. niger was very recently shown to create a non-acidifying mutant with reduced production of citric and oxalic acid supporting the hypothesis that it is not only secondary metabolites LaeA regulates [30]. It is not only in Aspergillus species that LaeA has a regulatory effect.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…These uncharacterized MRB mutants were cryogenically stored, awaiting a faster and more economical strategy for identification. Whole-genome sequencing has been used to identify mutant alleles in multiple model organisms (27)(28)(29), including several fungi (30)(31)(32)(33)(34)(35). Here we describe our success in utilizing next-generation sequencing of mutants using Illumina and Ion Torrent platforms to quickly and effectively identify the genetic basis of 12 of the remaining MRB mutants.…”
Section: Importancementioning
confidence: 99%
“…Because of its importance for both enzyme and organic acid production, multiple strains of A. niger have sequenced and analysed (Pel et al 2007). The reference sequence data from these strains has been critical for development of ‘fast forward’ genetic approaches for association of genes with mutant phenotypes (Niu et al 2016a, 2016b). All of this has built upon early sharing of research tools.…”
Section: Aspergillus Speciesmentioning
confidence: 99%